Frequency of Hyponatremia in Patients with Tuberculosis Bacterial Meningitis: A Cross Sectional Study - Yar Muhammad Tunio, Ruqayya Farhad, Rizwan Channa, Muhammad Adnan Bawany, Raja Ravender, Muhammad Kaleem, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim:To determine the frequency of hyponatremia in patients with Tuberculosis Bacterial Meningitis Study Design: Cross sectional study Place and duration: This study was conducted at Gambat Institute of Medical Sciences Gambat Khairpur Pakistan from June 2020 to June 2021. Methodology:The study included 169 patient. Each patient was questioned for their medical history and demographic data and this information was analyzed using the Statistical Package for Social Sciences (SPSS) version 22.0. These simple statistics included the age, height, and weight of the patients. It also factored in their Glasgow Coma Scale, how long their symptoms lasted for, and their serum sodium levels. Data taken for categorical variables was calculated and characterized using mathematical frequencies and percentages. These variables included data such as their gender, their smoking habits, diagnosed or undiagnosed hypertension and other medical phenomena’s inflicting the patient such as Type 2 Diabetes Mellitus, hyponatremia, the syndrome of inappropriate antidiuretic hormone, Cerebral salt wasting syndrome and finally the BMRC stage for the patients. The BMRC criteria was set for determining the stage of TBM in each patient, this criterion was created by the British Medical Research Council. Post stratification chi-square test was also taken for this study and only variables with a p-value of ≤0.05 were taken to be significant. Results: The results of our study concluded that 76 (45%) of the tuberculous bacterial meningitis patients suffered fromhyponatremia. Patients who suffered from syndrome of inappropriate antidiuretic hormone secretion and cerebral salt wasting syndrome were also recorded which were 13.2% and 26.7% respectively. This study population consisted of 60% males and 40% females where the average age of the patients was from 44 to 48 years. The mean duration of the symptoms was also recorded which displayed that the patient suffered from the disease for a period of three days to almost two weeks and the patients weighed between 68 to 87 kilograms. Conclusion: The results of our study proved the hypothesis that a great number of patients suffering from tuberculous bacterial meningitis are a victim of hyponatremia. If hyponatremia is not diagnosed and treated using the proper channels and techniques it can lead to grave consequences such as significant neurological conditions and death. It is important to keep track of the sodium levels in patients of tuberculous bacterial meningitis.